2013
DOI: 10.1074/jbc.m113.462648
|View full text |Cite
|
Sign up to set email alerts
|

“Snapshots” of Ispinesib-induced Conformational Changes in the Mitotic Kinesin Eg5

Abstract: Background: Ispinesib is a small molecule inhibitor of Eg5 and induces neck linker docking. Results: Ispinesib binding to Eg5 induces subsequent movement of switch II. Conclusion: Conformational changes in L5 can alter the orientation of the neck linker regardless of the state of the catalytic site. Significance: L5 is a key regulator of both the catalytic site and switch II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 34 publications
1
26
0
Order By: Relevance
“…In order to examine the importance of KIF11 in GBM pathophysiology, we utilized ispinesib, a cell permeable and highly specific small molecule inhibitor to KIF11 (31). We first determined the dose response relationships for cytotoxicity versus ispinesib concentration for matched TICs and non-TICs from 5 independent xenograft specimens after 72 hours of ispinesib exposure.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to examine the importance of KIF11 in GBM pathophysiology, we utilized ispinesib, a cell permeable and highly specific small molecule inhibitor to KIF11 (31). We first determined the dose response relationships for cytotoxicity versus ispinesib concentration for matched TICs and non-TICs from 5 independent xenograft specimens after 72 hours of ispinesib exposure.…”
Section: Resultsmentioning
confidence: 99%
“…Fitting to a persistent random walk model reveals that ispinesib reduces tumor cell velocity and not directional persistence. Of the 8 residues in KIF11 that interact with ispinesib, all are conserved in the KIF11 sequences from human, rat and mouse making it highly likely that the effects of ispinesib that we see in the rat ex vivo slice assay reflect direct inhibition of KIF11 (31). Associated with this block in dispersion is a change in tubulin polymerization and cell polarization with ispinesib.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A Model of L5 Function-Previous work from several laboratories has shown that the state of L5 affects nucleotide binding as well as MT affinity (4,6,7,10), implying a communication pathway connecting this loop to switch I and ␣4. Furthermore, the conformation of the ␣4 helix regulates both MT affinity and NL orientation (25).…”
Section: Features Of the Three Lifetime-defined States Can Be Mapped mentioning
confidence: 99%
“…A quinazolinone inhibitor of KSP (CK0106023) was tested in a SKOV3 human tumor xenograft model and showed inhibition of tumor growth comparable to that achieved with Paclitaxel. [9] One of the first targeted antimitotic agents, and the first KSP inhibitor to be studied in the clinic, is ispinesib (or SB-715992 Scheme 1), [10,11] a smallmolecule inhibitor of the KSP ATPase, uncompetitive with ATP and ADP. MK-0731 [12] is another potent small-molecule inhibitor of the KSP ATPase activity with > 20 000 fold selectivity for KSP over other kinesins (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%